Determination of Total Flavonoid Content in Local Sakura Leaf Extract or Small Bungur (Lagerstroemia indica L.) - Nur S. Damayanti; Sri H. V. Pulukadang; Sitti Aminah; Baharuddin Hamzah; Reny Reny (Universitas Tadulako, 2025)
The small bungur plant (Lagerstroemia indica L.) is one of the plants with potential as a medicinal plant. Almost all parts of this plant can be used, namely the leaves, stems, fruit and roots. Bungur leaves can be used for skin diseases, leaf powder for malaria, and decoction of old leaves for diabetes. Bungur leaves contain chemical compounds, one of which is flavonoids. This study aims to determine the total flavonoid content of extracts from young and old leaves of local cherry blossoms (small bungur), using UV-Vis spectrophotometry. The extraction method used was multistage maceration using three different solvents: hexane (nonpolar), ethyl acetate (semipolar), and methanol (polar). The results showed that the average total flavonoid content of young leaf extracts and old leaves of small bungur, measured by UV-Vis spectrophotometry at a maximum wavelength of 410 nm, was 8.810 mg/100g and 7.301 mg/100g, respectively. Among the three solvents used, extracts of young and old leaves of small bungur using hexane and ethyl acetate do not contain flavonoids, whereas extracts of young and old leaves of small bungur using methanol do.